Safety and effectiveness of the Kaiser Permanente early-onset neonatal sepsis calculator in Qatar - Paraparambil Vellamgot, Anvar; Thyvilayil Salim, Sajid; Salameh, Khalil; Kurunthattilthazhe, Sudheer Babu; Elikkottil, Abdurahiman; Habboub, Lina; Pattuvalappil, Rajesh; Joseph, Biny Elizabeth (Frontiers in Pediatrics, 2025)
IntroductionEarly-onset neonatal sepsis is a significant cause of neonatal morbidity and mortality worldwide. Although sepsis rates are declining, neonatal antibiotic use remains high. The early-onset sepsis risk calculator, endorsed by the American Academy of Pediatrics, is one of three evidence-based methods for identifying at-risk babies. This study retrospectively compared the calculator to the existing categorical approach.ObjectivesThe primary objective was to compare the effectiveness of the calculator with the existing categorical approach in identifying sepsis cases within the first 12 h of life. Secondary aims included describing the calculator's recommendations and identifying predictors of missed cases.MethodsWe retrospectively analyzed cases of early-onset sepsis in late-preterm and term infants born in Qatar between 2015 and 2022. We compared the calculator's predicted effectiveness to the current categorical approach.ResultsAmong 179,147 live births, 157 cases were identified (0.88 per 1,000). Of 105 cases (≥34 weeks), the calculator recommended antibiotics at birth in 37.1% (95% CI: 27.8%–46.4%) compared to 52% (42.9%–62.0%) by the categorical approach (p < 0.01), missing 16 cases. By 12 h, it identified 58.1% vs. 72.5% by the categorical approach (p < 0.01), missing 15 cases. Overall, the calculator missed six more cases than the categorical approach.ConclusionsThe calculator identified fewer cases and delayed treatment in some neonates compared to current practice. It should be used cautiously, tailored to local risks and clinical context, with close postnatal monitoring. Additional local prospective studies are necessary to improve EOS management and reduce unnecessary antibiotic use.